Bordetella pertussis targets the basolateral membrane of polarized respiratory epithelial cells, gets internalized, and survives in intracellular locations - Baroli, Carlos Manuel (2023)
The airway epithelial barrier is a continuous highly organized cell layer that separates the exterior from the underlying mucosal tissue, preventing pathogen invasion. Several respiratory pathogens have evolved mechanisms to compromise this barrier, invade and even reside alive within the epithelium. Bordetella pertussis is a persistent pathogen that infects the human airway epithelium, causing whooping cough. Previous studies have shown that B. pertussis survives inside phagocytic and nonphagocytic cells, suggesting that there might be an intracellular stage involved in the bacterial infectious process and/or in the pathogen persistence inside the host. In this study we found evidence that B. pertussis is able to survive inside respiratory epithelial cells. According to our results, this pathogen preferentially attaches near or on top of the tight junctions in polarized human bronchial epithelial cells and disrupts these structures in an adenylate cyclase-dependent manner, exposing their basolateral membrane. We further found that the bacterial internalization is significantly higher in cells exposing this membrane compared with cells only exposing the apical membrane. Once internalized, B. pertussis mainly remains in nondegradative phagosomes with access to nutrients. Taken together, these results point at the respiratory epithelial cells as a potential niche of persistence.